Socio-Economic Changes in Fishing Communities of The Village of Kedungrejo Sub-district Muncar Banyuwangi on 2000-2015 - Purwati, Magdalena Yuli; Sugiyanto, Sugiyanto; Marjono, Marjono (History Education, University of Jember, 2017)
The research is based on socio-economic change of Kedungrejo fishermen Muncar districts Banyuwangi. Government policies are related to UU No. 22 Tahun 1999 about local government authority for te management of natural resources that have the impact to the living of communities of fishermen. The research has purposed to know about socio-economic changes of Kedungrejo Fishermen that related to the causes and forms of change of that communities.The method that used in the research is the method of writing history with heuristic stage, critic, interpretation, and historiography. The government policies as a starting point to change have positive and negative impacts.The change of Kedungrejo Fishermen can be reviewed from education and income to the communities. The education level of fishermen has increased 68,93% on 9 years compulsory education program that implemented by the government. At the level of income of fishermen increased about 30%-40% are realized in the home of fishermen and vehicles owned by fishermen. Keywords: Socio-economic change, the fishermen community, and Kedungrejo fisherman